Eps8 regulates hair bundle length and functional maturation of mammalian auditory hair cells. - Valeria Zampini; Lukas Rüttiger; Stuart L Johnson; Christoph Franz; David N Furness; Jörg Waldhaus; Hao Xiong; Carole M Hackney; Matthew C Holley; Nina Offenhauser; Pier Paolo Di Fiore; Marlies Knipper; et al. (PLoS Biology)
Hair cells of the mammalian cochlea are specialized for the dynamic coding of sound stimuli. The transduction of sound waves into electrical signals depends upon mechanosensitive hair bundles that project from the cell's apical surface. Each stereocilium within a hair bundle is composed of uniformly polarized and tightly packed actin filaments. Several stereociliary proteins have been shown to be associated with hair bundle development and function and are known to cause deafness in mice and humans when mutated. The growth of the stereociliar actin core is dynamically regulated at the actin filament barbed ends in the stereociliary tip. We show that Eps8, a protein with actin binding, bundling, and barbed-end capping activities in other systems, is a novel component of the hair bundle. Eps8 is localized predominantly at the tip of the stereocilia and is essential for their normal elongation and function. Moreover, we have found that Eps8 knockout mice are profoundly deaf and that IHCs, but not OHCs, fail to mature into fully functional sensory receptors. We propose that Eps8 directly regulates stereocilia growth in hair cells and also plays a crucial role in the physiological maturation of mammalian cochlear IHCs. Together, our results indicate that Eps8 is critical in coordinating the development and functionality of mammalian auditory hair cells.